Role of DNA Fingerprinting in Disputed Paternity - Mishra, Amarnath; Sathyan, Sukumaran (Med Phoenix, 2017)
The use of DNA fingerprinting in solving crime is proving to be as revolutionary as the introduction of fingerprint evidence in court more than a century ago. It has emerged as one of the most powerful tools available for solving many medical as well as legal complexities. DNA fingerprinting plays an important role in the establishment of the paternity of an individual. Most of cases regarding disputed paternity arise in the context of affiliation orders, divorce proceedings and questioned legitimacy, may also be used to find out paternity in cases of inheritance, guardianship, maintenance, legitimacy, adultery or fornication. The present work was done to solve the paternity dispute. MED Phoenix Volume (1), Issue (1) July 2016, page: 44-46